Land Lease Markets and Agricultural Efficiency in Ethiopia. - Pender, J; Fafchamps, M (2006)
This paper develops a theoretical model of land leasing that includes transaction costs of enforcing labour effort, risk pooling motives and non-tradable capital inputs. We test the implications of this model compared to those of the "Marshallian" (unenforceable labour effort) and "New School" (costlessly enforceable effort) perspectives using data collected from four villages in Ethiopia. We find that land lease markets operate relatively efficiently in the villages studied, supporting the New School perspective. We find that other household and village characteristics do affect input use and output value, suggesting imperfections in other factor markets.